An appraisal of Rodwell Samkange a choral composer in Zimbabwe - Mabika, Mavonei C. (Midlands State University, 2018)
The study focused on the factors that inspired Rodwell Samkange to engage on the journey of choral composing and factors that influenced his style of composing. It aimed at analysing three of the composer’s repertoires which are Zvainge Pane chakatigara, Zimbabwe yakanaka and Pvumvu. The study sought to analyse the three pieces looking closely at the taxonomies of music used. Data was extracted through interviews and content analysis. The sample size was taken from all the music pieces composed by the composer from the year 1972 when he started composing to date. Purposive sampling was used hence the composer Rodwell Samkange was found relevant to the study and three of his pieces were also found relevant. The study found out that Rodwell Samkange was inspired by a number of things which include the family that he grew in, Caluza a South African composer, the innate behaviour and the revelation from dreams. His style of composing was also influenced by his guitar background, music education, Christian background, Caluza the South African composer and both exotic and internal cultural experience. The research also reviewed that different taxonomies of music were employed by the composer. These include harmonic device, melodic devices, structural devices and textural devices. These were all found to be influenced by the composer’s education, Christian background, and cultural experiences. Other composers should try and copy composing techniques from composers like Samkange who has sufficient knowledge required for one to be prominent composer. The works of Samkange should be documented for use by future generations.